Visceral-to-subcutaneous fat ratio and risk of gallstones in Korean men: an observational study of 4,914 cases - So, Hoonsub; Jeon, Young-Jee; Lim, Doo-Ho (Frontiers in Medicine, 2025)
IntroductionGallstones are a prevalent gastrointestinal disorder influenced by metabolic factors and obesity. Visceral adiposity is metabolically active and proinflammatory, yet the role of the relative distribution of visceral and subcutaneous fat, quantified as the visceral-to-subcutaneous fat ratio (VSR), in gallstone formation remains unclear. This study aimed to investigate the association between VSR, measured by computed tomography (CT), and the prevalence of gallstones in Korean men.MethodsThis retrospective cross-sectional study included 4,914 Korean men who underwent both abdominopelvic CT and ultrasonography as part of routine health examinations. Visceral and subcutaneous fat areas were quantified at the L3 vertebral level using CT images, and participants were categorized into quartiles based on the VSR. Logistic regression analyses were conducted to evaluate the association between VSR and the prevalence of gallstones, adjusting for age, body mass index (BMI), lifestyle factors, comorbidities, and biochemical markers.ResultsThe mean age and BMI were 52.3 ± 9.3 years and 24.6 ± 2.9 kg/m2, respectively. Gallstone prevalence increased progressively across VSR quartiles, from 4.0% in the lowest quartile to 7.6% in the highest (p < 0.001). In fully adjusted models, men in the highest VSR quartile had 1.6-fold higher odds of having gallstones compared to the lowest quartile (OR 1.596, 95% CI 1.074–2.373, p = 0.021).ConclusionA higher VSR, reflecting a predominance of visceral over subcutaneous fat, was independently associated with an increased risk of gallstones in Korean men. These findings highlight the importance of abdominal fat distribution, beyond overall obesity, in gallstone pathogenesis. The VSR may serve as a valuable imaging biomarker for identifying men at elevated risk of developing gallstones.